Burn severity in Kuala Langat forest using : remote sensing technique / Mahfuzah Jaffar - Jaffar, Mahfuzah (2018)
Fire severity can be mapped using Landsat satellite imagery to detect changes in forestfired structures. The purpose of this study is to study the severity of the burn using remote sensing techniques. The objective of this study is to identify the severity of fire in Kuala Langat forest, to determine the surface temperature and to determine the greenness that grows in the forest of Kuala Langat. Landsat satellite image is used to calculate the Normalized Burn (NBR) ratio referring to the near infrared range (NIR) and the short wave infrared range (SWIR). Changes in NBR from prefire to postfire determine the value of dNBR to estimate the severity of the burned forests. Surface temperatures are identified in the Kuala Langat Forest during dry and regular seasons. Normalized Difference Vegetation Index (NDVI) is used to study images only after the fire and image 2 years after the fire to determine the level of green forest of Kuala Langat. All methods are processed in Erdas 2014 and ArcGIS versions. Burned severity classes maps, land surface temperature maps and map of Normalized Difference Vegetation Index Kuala Langat Forest are produced.